2019
DOI: 10.1016/j.mce.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oxytocin on eating behaviours and stress in women with bulimia nervosa and binge eating disorder

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
10
2
Order By: Relevance
“…That is, one might reasonably hypothesise that reduced hedonic food consumption would be associated with less attentional and motivational orientation to food stimuli. However, previous studies finding a suppression of hedonic eating reported this effect in male participant samples, 20,24,36 although no effect of oxytocin on feeding was found in the current sample of female participants 31 . An accumulating range of studies has found mixed effects of oxytocin on eating in women, both with and without eating disorders, 17,27 therefore suggesting that the inhibitory effect of oxytocin on hedonic eating and orienting to food stimuli may be sex‐specific in humans.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…That is, one might reasonably hypothesise that reduced hedonic food consumption would be associated with less attentional and motivational orientation to food stimuli. However, previous studies finding a suppression of hedonic eating reported this effect in male participant samples, 20,24,36 although no effect of oxytocin on feeding was found in the current sample of female participants 31 . An accumulating range of studies has found mixed effects of oxytocin on eating in women, both with and without eating disorders, 17,27 therefore suggesting that the inhibitory effect of oxytocin on hedonic eating and orienting to food stimuli may be sex‐specific in humans.…”
Section: Discussioncontrasting
confidence: 62%
“…Following the completion of the bogus taste test, the three bowls of food were brought to a separate room, out of sight of the participant, where a research assistant weighed the remaining food in each bowl and subtracted this amount from the initial weight of each type of food. The effect of oxytocin on the quantity of food eaten is reported elsewhere 31 …”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that a divided dose of intranasal OT (64 IU) modulates risk-taking behaviour in women with BN/BED 45 and increases vigilance towards food, vs. neutral, images in a dot probe task in both women with and without BN/BED 46 . However, in the same cohort of women with BN/BED, we failed to find any effect of the same divided dose of intranasal OT (64 IU) on eating behaviour or stress response 47 . Apart from the lack of clarity regarding the effectiveness of intranasal OT to improve eating symptomatology in patients with BN/BED, it is also not clear which brain circuits intranasal OT targets in BN/BED patients.…”
Section: Introductioncontrasting
confidence: 55%
“…In addition to their classical roles in reproduction, stress and water balance, oxytocin and vasopressin have roles in energy homeostasis . Both central and peripheral oxytocin administration exert anorexigenic effects, increase energy expenditure and induce lipolysis . Peripheral administration of both oxytocin and vasopressin can induce the release of insulin from the pancreas and systemically administered oxytocin in humans (administered intranasally) has been reported to curb the meal‐related increase in plasma glucose, as well as to improve β‐cell responsivity and glucose tolerance in healthy men .…”
Section: Introductionmentioning
confidence: 99%